PENERAPAN MODEL PROJECT-BASED LEARNING TERHADAP PENINGKATAN KARAKTER GOTONG ROYONG PESERTA DIDIK MADRASAH IBTIDAIYAH - Hamidah, Allinda (Universitas Islam Darul 'Ulum Lamongan, 2024)
This research aims to determine the use of the Project Learning Model to improve the Mutual Cooperation Character of Class IV students at elementary school Mathlabul Huda Karangasem Lamongan in learning Natural and Social Sciences, This research uses quantitative methods, an experimental approach with a Pre-Experimental Design type in the form of a group Pretest-Posttest Design. Using analytical techniques: (1) Descriptive statistical analysis, (2) Normalized Gain Test (N-Gain Score), (3) Hypothesis Testing, (simple linear regression), Effectiveness of using the Project Based Learning Model in improving students' cooperative character measured using the N-Gain Score test and obtained an average N-Gain Score value of 71%, so it can be concluded that it is quite effective. In the simple linear regression test, a significance value (Sig.) was obtained of 0.009 < 0.05, which means the use of the model Project Based Learning in science learning has a significant influence on improving the cooperative character of class IV students at elementary school Mathlabul Huda Karangasem, Babat, Lamongan.